The possibility of documentation through animation: A comparative study of the animated short Pica-Don and other artworks addressing social/historical issues. Issue 1 (1st December 2018) - Nagao, Makiko
In previous studies on animated documentary, discussions have mainly focused on the capacity of animation to supplement or enhance recorded audio-visuals. Thus, while animation is highly regarded for its ability to broaden and enrich documentary expression, it appears to be placed in the secondary or subsidiary position to recorded audio-visuals. Taking a different viewpoint, this article explores the potential of animation to operate by itself as a representational medium, through a comparative study of the animated short Pica-Don (Kinoshita, 1978) and four artworks of other genres, all of which refer to real social/historical events. Pica-Don attempts to present a general description of the event of 6 August 1945 using animation, music and sound effects, based on thorough investigation of historical documents as well as the drawings, writings and testimonies of survivors. As the film refrains from using language, it is not endowed with specific detail. Instead, the event of that day are condensed intensively, causing the viewer to feel as though they are going through a simulated experience. This article explores how documentation is made possible in animation, and considers the potential capabilities that are unique to animation in this regard. It argues that subjective animation may be considered another form of documentation through presenting a general description of a social/historical event.